Determinants of Nurses’ Clinical Performance in Implementing Nursing Care Standards within Inpatient Services: A Practice-Based Perspective at Kota Tinggi Hospital - Alex, Viji; Zah, Norazalina Mohamad (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to analyze the determinants of nurses’ clinical performance in implementing nursing care standards within inpatient services at Kota Tinggi Hospital, Johor.Methodology: A quantitative analytical study with a cross-sectional design was conducted involving 98 nurses selected through total sampling. Data were collected using structured questionnaires and observation checklists. Statistical analysis included univariate, bivariate (Chi-square), and multivariate (logistic regression) analyses.Main Findings: The findings revealed that knowledge (p=0.001), motivation (p=0.002), leadership (p=0.000), and compensation (p=0.003) were significantly associated with clinical performance. Leadership was identified as the most dominant factor (OR=3.86). A majority of nurses (64.3%) demonstrated high clinical performance, although a notable proportion (35.7%) showed lower performance.Novelty/Originality of this study: This study provides a practice-based and integrative analysis of multiple determinants influencing nurses’ clinical performance in inpatient settings, emphasizing the role of leadership in bridging the gap between nursing standards and real clinical implementation.